Teacher Personality and the Perceived Socioeconomic Gap in Student Outcomes - Giorgio Brunello; Clementina Crocè; Pamela Giustinelli; Lorenzo Rocco (Institute of Labor Economics (IZA), 2024)
We randomly assign student profiles to teachers and elicit teachers' beliefs about the student's likelihood of success in alternative high school tracks. We document a large and statistically significant gradient in teachers' beliefs about students' high school prospects with respect to students' socioeconomic background (SEB), ceteris paribus. We find that this gradient varies with teacher's personality, a hard-to-observe and understudied teacher trait. Specifically, higher levels of teacher's extraversion and openness are associated with a steeper negative SEB gradient in teachers' beliefs about students' success prospects in an academic track. Conversely, more conscientious and agreeable teachers assign to low-SEB students, on average, a higher probability of success in a vocational track. We discuss some policy implications of our findings.
Keywords: I20; I24; 330; teachers' beliefs and personality; choice of high school tracks; Italy